Identification of Corporate Social Responsibility Actions of Microenterprises in Ciudad Ixtepec, Oaxaca - Villalobos Martínez, Andrea; Hernández Nolasco, Lilian; Cruz Celis, Felipe de Jesús (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2024)
OBJECTIVE: To identify Corporate Social Responsibility (CSR) actions in microenterprises in the commercial sector in Ciudad Ixtepec, Oaxaca.MATERIAL AND METHOD: The study is mixed type, with an exploratory scope. The data collection tools proposed are: a documentary review, direct observation and application of surveys to 64 economic entities.RESULTS: The microenterprises that participated in this study have moderate CSR actions in the internal dimension, and in the external dimension there are no CSR practices in the economic, social and environmental axis in relation to the immediate environment.CONCLUSIONS: The CSR of microenterprises is observed in voluntary and informal actions of administrative management and in seeking social well-being in its relationship with the immediate environment as requested. Therefore, The CSR in microenterprises works differently from other levels of the organization, being limited to the conditions and actions of each economic entity.
Keywords: Microenterprise; Economy; Corporate social responsability.